3D food printing: paving way towards novel foods - SINGHAL,SOMYA (2020)
Abstract 3D food printing, a part of additive manufacturing technique is used to modify the process of the food manufacturing in terms of color, shape, flavor, texture and nutrition. It liberates the user to identify and modify their meal according to one’s desire, matching to the very minute details. Currently, it is used in decorating and fabricating, food products such as chocolate, cookies and cakes. The process of printing foods depends on several factors such as the physical state of food (whether powder, liquid or semi-solid), size and shape of the syringes to be used and the composition of the ingredients such as carbohydrates, proteins and fats. Apart from the use of 3D food printing for fabrication, it can also play an important role in solving malnutrition by enhancing the nutritional profile of the meal. The objective of this review is to highlight the different methods used in 3D food printing, 3D food printers, benefits of 3D food printing and challenges faced while food printing. Moreover, the paper discusses the applications of 3D food printing and its scope in the near future.